Foreign policy discourses of the Obama years - Kovács, Melinda (Lexington Books, 2017)
Empirical case studies demonstrate how foreign policy actions depend on discourse in order to appear possible and to become plausible. This study of discourse is offered as a tool for assessing presidential administrations.